Application of data mining as a tool in computer science. (July 2020) - Velásquez-Pérez, T; Camargo-Pérez, J A; Quintero-Quintero, E L
Abstract: Computational science involves a systemic approach for adequate management of both information and knowledge; through theories of information and computation. Today trends such as big data and data mining emerge, with which behavior patterns previously only visible to the human eye can be established. This article, part of the analysis of big data, based on research found on the science websites, whose objective was based on knowing the conceptual evolution of Big data as well as the search for statistically regular behaviors over time in different elements related to the production and consumption of scientific information. For this study, data mining will be specified for Big data analysis, resulting in instructions to identify and understand trends and patterns within the different research areas.